Identification of a peroxisome proliferator-responsive element upstream of the gene encoding rat peroxisomal enoyl-CoA hydratase/3-hydroxyacyl-CoA dehydrogenase. - Zhang, B (1992)
Ciprofibrate, a hypolipidemic drug that acts as a peroxisome proliferator, induces the transcription of genes encoding peroxisomal beta-oxidation enzymes. To identify cis-acting promoter elements involved in this induction, 5.8 kilobase pairs of promoter sequence from the gene encoding rat peroxisomal enoyl-CoA hydratase/3-hydroxyacyl-CoA dehydrogenase (EC 4.2.1.17/EC 1.1.1.35) was inserted upstream of a luciferase reporter gene. Transfection of this expression vector into rat hepatoma H4IIEC3 cells in the presence of ciprofibrate resulted in a 5- to 10-fold, cell type-specific increase in luciferase activity as compared to cells transfected in the absence of drug. A peroxisome proliferator-responsive element (PPRE) was localized to a 196-nucleotide region centered at position -2943 from the transcription start site. This PPRE conferred ciprofibrate responsiveness on a heterologous promoter and functioned independently of orientation or position. Gel retardation analysis with nuclear extracts demonstrated that ciprofibrate-treated or untreated H4IIEC3 cells, but not HeLa cells or monkey kidney cells, contained sequence-specific DNA binding factors that interact with the PPRE. These results have implications for understanding the mechanisms of coordinated transcriptional induction of genes encoding peroxisomal proteins by hypolipidemic agents and other peroxisome proliferators.